Microstructure evolution of Al-7wt%Si-2wt%Fe alloy processed by high-pressure torsion - Jittraporn Wongsa-Ngam; Chakkrist Phongphisutthinan; Terence G. Langdon (My University, 2018)
The microstructure evolution of an aluminum silicon-based alloy after severe plastic deformation processing was examined. An aluminum silicon-based alloy; Al-7wt%Si-2wt%Fe, was processed by the severe plastic deformation technique called high-pressure torsion at room temperature under a high pressure of 6.0 GPa and rotational speed of 1.0 rpm with numbers of revolution up to 5 turns. Microstructure evolution, especially intermetallic phase, was observed using an optical microscope and a scanning electron microscope (SEM). The effects of high-pressure torsion on the Fe intermetallic compounds in Al-Si alloy were investigated. It was found that the intermetallic particles decreased in size with increasing imposed strains.
Keywords: Severe Plastic Deformation; Microstructure and mechanical properties